An economic perspective on oceans and human health. (11th August 2015) - Legat, Audrey; French, Veronica; McDonough, Niall
Abstract : Human health and wellbeing are intrinsically connected to our seas and oceans through a complex relationship comprising both positive and negative influences. Although significant public health impacts result from this relationship, the economic implications are rarely analysed. We reviewed the literature to assess current knowledge on the economic valuation and impacts of ocean and human health interactions in a European context. Quantitative analyses on the economic impacts of varying ocean-health interactions were limited. Common challenges to economic assessment included the difficulty in obtaining estimates for indirect healthcare costs, under-reporting of illness and the lack of standardization of surveillance data on illnesses, when available. It was also evident that non-market values, such as health promotion and psychological benefits are underrepresented in economic assessments, most likely because of the lack of standardized valuation methods for such non-market values. We provide recommendations to improve knowledge of ocean and human health linkages and progress future assessment of its economic implications in Europe.